O potrebe spoznávat' pravdu a obnovovat' poriadok - Mačák, Ivan (Traditiones (Ljubljana), 1999)
In his article the author argues that romantic explanations are not the only option in the research of folk art; there is also an intuitive need to learn the truth and to restore order. He attempts the conceptes of communication and culture
Keywords: ljudska umetnost; kultura; culture; komunikacije